How Relevant is Justice Cardozo’s “Book of Wisdom” to Patent Damages? - Sidak, J. Gregory (Science and Technology Law Review, 2016)
Section 284 of the Patent Act specifies that damages for patent infringement must be “adequate to compensate for the infringement, but in no event less than a reasonable royalty.” To determine a reasonable royalty, courts often rely on the hypothetical-negotiation framework, which aims to determine a royalty upon which the infringer and patent holder would have agreed, had they negotiated a license for the use of the patented technology immediately before the infringement began. Determining a reasonable royalty requires a court to return in time to the moment of the hypothetical negotiation and account for the limited information available to the parties at that time. That limited information would have affected the parties’ negotiating positions and consequently the outcome of the hypothetical negotiation. Conversely, because the parties at the time of the hypothetical negotiation would not have known information that became available only after the infringement began, information that postdates the hypothetical negotiation would not have affected a hypothetically negotiated reasonable royalty. Some commentators have proposed, nonetheless, that courts should allow a reasonable-royalty calculation to incorporate information that postdates the hypothetical negotiation. The proposition that one can use such information to inform a court’s determination of a reasonable royalty—called the “book of wisdom” doctrine—originated in Justice Benjamin Cardozo’s evocative but characteristically Delphic phrase in Sinclair Refining Co. v. Jenkins Petroleum Process Co. in 1933. When translated into plain English, Justice Cardozo’s reasoning is seen to rest on fallacious economic reasoning. Not surprisingly, the party that benefits the most from the facts discovered after the date on which the defendant incurred liability commonly invokes the “book of wisdom.” However, basing the determination of a reasonable royalty on information that postdates the hypothetical negotiation would violate fundamental legal and economic principles for calculating patent damages. The Federal Circuit has emphasized that courts should calculate a reasonable royalty on the basis of the parties’ expectations at the time of the hypothetical negotiation, not on post-infringement facts. The Federal Circuit has allowed reliance on post-infringement data only when they are necessary to infer the parties’ bargaining position at the time of the hypothetical negotiation. Outside this exception, there is no valid legal or economic justification to rely on postinfringement data when calculating a reasonable royalty. Rather the contrary: calculating a reasonable royalty based on post-infringement data would give an infringer a free option to use the patent and later ask the court to determine a reasonable royalty on the basis of the infringer’s actual, rather than expected, use of the patent. Infringing the patent would carry no risk of overpaying for the use of the patent if the infringer’s actual sales were less than the initial expectations. Basing the calculation of a reasonable royalty on information that postdates the hypothetical negotiation would thus create a perverse incentive for the potential licensee to infringe the patent rather than to negotiate a license in a timely manner.